Case Study on Teachers' Competence at Public Elementary School 147 Palembang - Sari, Nabella Aulia; Sharma, Mani Ram; Lestari, Neta Dian (PPSDP International Journal of Education, 2025)
This study aims to analyze teacher competency at SD Negeri 147 Palembang through a qualitative case study. The teacher competency that is the focus of this study includes four main aspects: pedagogical, professional, personality, and social competency. Data were collected using two main techniques, namely in-depth interviews with the principal and questionnaires distributed to teachers. Interviews with the principal were used to obtain a general view of teacher performance and competency development strategies in schools, while questionnaires were designed to evaluate teachers’ perceptions of their respective competencies. The results of the study indicate that teachers at SD Negeri 147 Palembang have good competency, especially in personality and social aspects, which are reflected in the high level of discipline and effective communication with students and colleagues. However, improvements are still needed in the use of technology in learning and the application of more innovative teaching methods and strengthening communication with parents of students. These findings indicate that ongoing training is needed to improve the quality of teaching and professional skills of teachers at SD Negeri 147 Palembang. This study is expected to be a reference for policy making in efforts to improve teacher competency in public elementary schools in Indonesia.